Distribution of Soil Density Values in Various Agricultural Lands in Jatipurno Sub-district, Indonesia - Mujiyo, Mujiyo; Nugraha, Meilissar Salahuddin Alif Rahman; Suyana, Jaka; Herawati, Aktavia; Nugroho, Fajar (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2026)
Soil density is a crucial parameter for soil physical health. It influences the ability of plant roots to penetrate the soil, which in turn impacts the plant's absorption of water and nutrients. The research was conducted in Jatipurno Subdistrict, Wonogiri Regency, to determine the distribution of soil density, the influence of sources of diversity, the determinants of soil density, and recommendations for land use. Descriptive exploratory research through survey and laboratory analysis was employed in this study, with soil density measured using the Dynamic Cone Penetrometer (DCP). The quite high soil density class covers 2,631.28 ha (60.51%), and the high soil density class covers 1,716.87 ha (39.49%). Land use did not significantly affect soil density, whereas soil type, slope gradient, and rainfall did. Soil density values have a significant positive correlation with bulk density (r = 0.862; P-value = 0.000; N = 45) and texture (r = 0.572; P-value = 0.000; N = 45), and have a significant negative correlation with water content (r = -0.457; P-value = 0.002; N = 45), porosity (r = -0.699; P-value = 0.000; N = 45), and organic C (r = -0.404; P-value = 0.006; N = 45). These five parameters were selected as determining factors, increasing bulk density and texture (clay content), and decreasing water content, porosity, and organic C will increase soil density. Improved land management, based on these determining factors, is needed to increase agricultural land use for sustainable agricultural production, such as mulching, increasing organic matter content, and minimal tillage to maintain soil surface moisture.